Essentials of International Relations. - Mingst, Karen A. (New York, W.W. Norton & Co., 2008)
Taking a balanced view of major theoretical approaches, including liberalism, Marxism, feminism, and constructivism, Mingst (University of Kentucky) provides analytical tools students need to understand world political affairs at the individual, state, and international system levels. Updated to reflect recent developments and debates in world politics, this third edition provides expanded coverage of intergovernmental organizations, such as the UN, and of both terrorist and peaceful nongovernmental organizations.
Include Bibliography Reference and Index Material.
Keywords: International relations; International Politik; international relations